History of the School of Application at FEUSP (1976-1986) : José Mário Pires Azanha's contribution to school culture - Gordo, Nívia; Boto, Carlota (Faculdade de Educação/Universidade Estadual de Campinas, 2021)
From 1976 to 1986, the School of Application (EA), linked to FEUSP, was guided by José Mário Pires Azanha with the aim of turning it into a common school, similar to the public school. Given the relevance of Azanha's performance with regard to the reorganization and functioning of EE in the various aspects of a technical-administrative and pedagogical nature and the good results achieved in learning, the objectives of this report are proposed: to describe: the history of EE in said period; Azanha's position in the face of the pedagogical renewal movement in the 70s and 80s; and identify aspects of theory and practice developed in EE that may be viable in public schools in this state.